Impact of Brix 3000 and conventional restorative treatment on pain reaction during caries removal among group of children in Baghdad city - Mafaz M Ismail; Aseel H Haidar (College of Dentistry/ University of Baghdad, 2019)
Background: Pain and the usage of local anesthetic agents are still real problem in pediatric dentistry, for these reasons, the use of minimal invasive dentistry (MID) in regard to the patient comfort is important especially for children, anxious and uncooperative patients. Chemomechanical caries removal (CMCR) methods involve the selective removal of the carious dentine hence it avoided the painful removal of the sound dentine and the anxiety resulted due to the vibration of the hand piece which is also decreased thus it appears to be more acceptable and comfortable to the patient. Aims of this study: This study was conducted among group of children to assess and compare the anxiety rating scale (during and after treatment) between the use of a recent chemomechanical caries removal method (by using Brix 3000) and the use of rotary instruments (using the ceramic bur). Materials and methods: Thirty pediatric patients aged between 8-12years, with bilateral occlusal carious permanent molars (extending into dentin) were selected for this study. Carious lesions were removed using Brix 3000 (CMCR) on one side and rotary instruments on the contra lateral side. Both cavities were restored with light cured composite filling. Anxiety scores were determined using Frankle rating scale (1962) during and after the period of caries removal. Results: The anxiety rating scale during the period of treatment showed the percentage of the negative behavior in the CMCR method was less than the percentage of the ceramic bur reverse the positive and definitely positive, which means that the new CMCR agent (Brix 3000) was more comfortable than the conventional rotary instrument (ceramic bur), that reduced the need for local anesthesia and the use of the drill. While after the treatment there is no big difference in the acceptance of the patients in two groups. Conclusion: Brix 3000 gel as a CMCR is an effective alternative method for caries removal, which appears to be more comfortable for the patients and more conservative